Classification of full-thickness rotator cuff lesions: a review. Issue 12 (1st December 2016) - Lädermann, Alexandre; Burkhart, Stephen S.; Hoffmeyer, Pierre; Neyton, Lionel; Collin, Philippe; Yates, Evan; Denard, Patrick J.
Abstract : Rotator cuff lesions (RCL) have considerable variability in location, tear pattern, functional impairment, and repairability. Historical classifications for differentiating these lesions have been based upon factors such as the size and shape of the tear, and the degree of atrophy and fatty infiltration. Additional recent descriptions include bipolar rotator cuff insufficiency, 'Fosbury flop tears', and musculotendinous lesions. Recommended treatment is based on the location of the lesion, patient factors and associated pathology, and often includes personal experience and data from case series. Development of a more comprehensive classification which integrates historical and newer descriptions of RCLs may help to guide treatment further. Cite this article: Lädermann A, Burkhart SS, Hoffmeyer P, et al. Classification of full thickness rotator cuff lesions: a review. EFORT Open Rev 2016;1:420-430. DOI: 10.1302/2058-5241.1.160005.